FAMILY AND FAMILY VALUES IN THE MINDS OF STUDENT YOUTH (USING THE CASE OF DAGESTAN) - Veresagina, A V; Gafiatulina, N H; Zagirova, E M (History, Archeology and Ethnography of the Caucasus, 2015)
Formation of new family relations and values in the Russian society has its own specific character, connected with regional, ethnocultural and sociocultural peculiarities of the Russian society, on the one hand, and with upward trends of globalization, on the other hand. The authors of the article analyze the way the students perceive family, its various forms, family values and problems in the sphere of family-marital relations in the modern Russian society. The authors come to the conclusion that family maintains the position of the most important value among the young people, and it is of crucial importance for the future of the Russian society, in spite of the fact that family space of modern Russia is rather pluralistic and includes variety of family patterns and forms.
Keywords: students; family; family values; family relations; Russian society